2023
DOI: 10.1038/s41598-023-30302-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the protective effects of fisetin against arsenic-induced reproductive toxicity in male rats

Abstract: Arsenic is one of the most hazardous environmental contaminants, which adversely affects the dynamics of male reproductive system. Fisetin (FIS) is a bioactive flavonoid, which is known to exert strong antioxidative effects. Therefore, the current research was planned to evaluate the alleviative efficacy of FIS against arsenic-induced reproductive damages. Forty-eight male albino rats were divided into 4 groups (n = 12), which were treated as follows: (1) Control, (2) Arsenic-intoxicated group (8 mg kg−1), (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Consistent with our observations, arsenic has been found to downregulate the mRNA expression of sf-1 and the steroidogenic enzymes in the testicular Leydig cells of mice [ 61 , 62 ]. Previous rodent studies also reported reduced expression of the gonadal 17β-hsd gene and a decrease in the plasma sex steroid levels following chronic treatment with arsenic [ 26 , 63 , 64 ]. Additionally, we also recorded a decreased expression of gonadotropin receptor genes ( Fshr and Lhr ) in the gonads of male and female zebrafish following chronic exposure to arsenic, which might be a consequence of the downregulation of the Fshβ and Lhβ genes in the brain, as suggested in mammalian studies [ 65 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with our observations, arsenic has been found to downregulate the mRNA expression of sf-1 and the steroidogenic enzymes in the testicular Leydig cells of mice [ 61 , 62 ]. Previous rodent studies also reported reduced expression of the gonadal 17β-hsd gene and a decrease in the plasma sex steroid levels following chronic treatment with arsenic [ 26 , 63 , 64 ]. Additionally, we also recorded a decreased expression of gonadotropin receptor genes ( Fshr and Lhr ) in the gonads of male and female zebrafish following chronic exposure to arsenic, which might be a consequence of the downregulation of the Fshβ and Lhβ genes in the brain, as suggested in mammalian studies [ 65 ].…”
Section: Discussionmentioning
confidence: 94%
“…A few previous studies conducted in fish also indicated the endocrine-disrupting effects of arsenic. For example, an in vitro study using a fish testicular culture system suggested that arsenic inhibits the synthesis of the androgenic sex hormone (11-ketotesterone), leading to decreased spermatogenesis in males [ 26 ]. In female oviparous vertebrates like fish, reproduction is regulated by the HPG-L (hypothalamus–pituitary–gonad–liver) axis, as the liver plays a primary reproductive function by synthesizing and secreting vitellogenin under estrogen stimulation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, according to a number of previous studies, including Ren et al [32], the antioxidant activity of fisetin was thought to be responsible for these protective effects. Fur-thermore, fisetin was observed by Ijaz et al [67] to enhance the enzymatic activity of reactive oxygen species, thiobarbituric acid reactive substance, glutathione, glutathione reductase, superoxide dismutase, and catalase. Moreover, Wang et al [68] reported that fisetin had anti-inflammatory and anti-fibrotic properties, hence, fisetin can protect the kidneys from developing fibrotic disorders.…”
Section: Discussionmentioning
confidence: 97%